Elementary school teachers' perception of artificial intelligence integration in curriculum management - Rusi Aliyyah; Rachmah Amalia (Journal of Educational Management and Instruction (JEMIN), 2025)
Curriculum management is a key element in ensuring effective and efficient teaching and learning processes in schools. With the emergence of digital transformation in education, artificial intelligence (AI) offers new opportunities to enhance curriculum planning, implementation, and evaluation. This study explores elementary school teachers’ perceptions of integrating AI in managing the Independent Curriculum in Indonesia. A qualitative design with a thematic analysis approach was employed. Data were collected through semi-structured interviews with 55 purposively selected teachers from West Java who have implemented the Independent Curriculum since 2021. Each interview lasted for 20–30 minutes and focused on four core aspects: urgency, strategies, challenges, and support for AI integration. The analysis was conducted using NVivo 12 to identify recurring patterns and themes. Findings reveal that teachers perceive AI as crucial for supporting the Pancasila Student Profile Strengthening Project (P5), providing greater autonomy for both students and teachers, refreshing the learning process, and enabling more contextual curriculum management. Teachers adopt various strategies such as aligning AI with curriculum principles, applying innovative learning approaches, and using AI to map students’ needs. However, challenges remain, including limited technological literacy, inadequate infrastructure, and time constraints. Support is mainly derived from training programs, teacher working groups, and school facilitators. The study concludes that AI integration holds strong potential to improve educational quality in elementary schools, but sustained capacity building, supportive policies, and adequate resources are essential for successful implementation.